Performance of Poultry Farmers in Agriculture Sector: A Case of the Poultry Farmers in Odiongan, Romblon - Falculan, Ken N.; Aungon, Cherelyn S. (PT FORMOSA CENDEKIA GLOBAL, 2023)
The results of this research will be able to describe the perceptions of poultry farmers regarding their level of satisfaction with regard to the availability of transport, land, interest, feed supply, market, foundation stock, finance, water, and pricing bodies by presenting the relationship between each of the selected societal characteristics of the poultry farmers and their perceptions of the performance of the poultry industry. The analysis revealed that market conditions and financing decisions satisfied poultry growers. Furthermore, the findings pointed out that poultry producers certainly lacked the required production capabilities. These abilities include the competence to establish and maintain an appropriate temperature, timely disease detection, timely stress detection, timely stress reduction, timely disease eradication, and timely categorization of death caused by feed/nutrition.